Fabrication of reinforced and toughened poly(lactic acid)/poly(butylene adipate‐co‐terephthalate) composites through solid die drawing process. Issue 36 (7th February 2020) - Zhang, Tongying; Wu, Pingping; Yang, Qi; Jiang, Jian
Abstract: In this study, poly(butylene adipate‐ co ‐terephthalate) (PBAT) was introduced to poly(lactic acid) (PLA) matrix to improve its inherent poor toughness. Besides, the orientation structure was also introduced via die drawing process to compensate for strength loss. The results indicate that die drawing process contributes to improve the mechanical properties of PLA. The tensile strength, modulus, and elongation at break of die‐drawn pure PLA increased by 76.6, 36.1, and 1, 375.0%, respectively, compared with those of isotropic PLA. Moreover, the tensile strength can be further improved by the addition of PBAT. The die drawing process can remarkably improve crystallinity, and the orientation factor is high when the PBAT content is less than 30 wt%. By combining the PBAT with highly oriented structure imported by die drawing process, it is possible to prepare simultaneously reinforced and toughened materials, which provides a new insight into the modification of PLA. Abstract : In this study, PBAT was introduced into PLA matrix through melt blending. After forming into sheet, the composites were drawn through a solid die drawing apparatus. Simultaneously reinforced and toughened materials were obtained. The tensile strength, modulus, and elongation at break of die‐drawn pure PLA increased by 76.6, 36.1, and 1, 375.0%, respectively, compared with those of isotropic PLA (60.6 MPa, 2, 235.4 MPa, 4.4%). Because the die drawing process can remarkably improve crystallinity and orientation. This provides a new insight into the modification of PLA.